Technical Performance Analysis of Iran Premier League Soccer Players in 2012-2013 Season - Javani Mohsen; Hamedinia Mohammadreza; Khodaei Kazem (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Background and purpose of study : analysis of IRAN premier league soccer players' technical performance in season 2012-2013, using a computerized match analysis system (Borhan Mobin Development Management Co, IRAN). Material and methods: in this study, data were obtained from 120 players, who performed in competitions 90 minutes. The players were classified into 3 positional roles: defenders, midfielders and forwards. Technical performance variables analysis included: total passes, total successful passes, pass accuracy, total shots; total shots to target, shot accuracy, ball interception and ball losses. The data were statistically analyzed by one-way ANOVA, Kruskal-Wallis, Mann-Whitney U and Tukey post hoc test. Results : The findings of this study showed that players performed about 45 passes per competition. Midfielders and defenders had significantly higher number of passes than forwards. Pass accuracy was about 67% and there were no significant differences between positional roles. Also, the players performed about 0.8 shots per competition, forwards and midfielders had significantly higher number of shots than defenders. Shot accuracy was about 31%; midfielders and forwards had significantly higher shot accuracy than defenders. Forwards showed significantly lower ball interception and higher ball losses than other positions. Conclusion : The result of this study showed that there were significant differences between some technical actions in positional roles. Therefore, coaches can use this information for individualization of training according to playing positions and for optimization of training in the amateur game.